Face Recognition Based Smart Attendance System - Chilme, Pravin Panditrao; Jaffarkhan, Pathan Naserkhan (International Journal of Computer Sciences and Engineering, 2020)
Daily participation of the student in the current academic program plays a significant role in measuring success and tracking efficiency. Calling people names or writing on papers are the traditional approaches used in most organizations that are very time consuming and vulnerable. This article describes the automated attendance management method, for convenience or data reliability. The project's key working theory is that, identifying and remembering a particular student. This project is built for attendance at school / college. This framework is based on the technique for camera known as facial recognition system. In the centre of the classroom above the black board facing the students, the camera should be attached. As per the timer set for class timing system. The camera takes the shot from the classroom. And this system plays a key role in the present situation of covid19 as it avoid from person to person contact. Which only captures students face by maintaining certain distance.